Developing Mobile Application For Generic Human-Machine Communication - Lau, Dick Mun (Universiti Sains Malaysia, 2018)
As the next industrial revolution, Industry 4.0 is an intelligent production incorporated with Internet of Things Remote (IoT), cloud technology and big data. This scenario requires real time applications which are important to monitoring system effectively, instantly, anywhere and anytime. A monitoring system application is designed and developed. The proposed system acts as the monitoring system based on Android platform to give convenience in accessing monitored parameters quickly on mobile devices anywhere at anytime. The application is built by using MIT App Inventor II and is applicable in any android mobile device. A graphical user interface (GUI) is developed as the monitoring system which exhibits the information gathered from the system. Its main functions are to display information, store data, alert system and allow information sharing among the users. Beside displaying the charts, the application enables the user to have the conversation with each other to communicate and discuss about any issues occured. The only condition required is the application supportability given by the android system over 3G/4G network or Wi-Fi connection. Finally, a pilot test will be tested on this application to understand its compatibility on old and new version of Android API.